NON-AGRICULTURALACTIVITIES IN RURAL SETTLEMENT HORTO AIMORES: PERFORMANCE OF VIVERDE AGROECOLOGICAL ASSOCIATION - Al Zaher, Camila [UNESP]; Perusi, Maria Cristina [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2015)
In rural areas the natural resource soil has been heavily depleted due to inadequate farm practices, which may result in chemical soil degradation, physical soil degradation and mostly results in social and economic fragmentation of peasant agriculture. These degradations impaired the agricultural production and consequently the maintenance of the settled families and in these situations are noted the presence of non-agricultural activities as a method of family ancillary income. In this context was formed the rural settlement Horto Aimores. It is located on the center of Sao Paulo state between the cities of Bauru and Pederneiras. This study aimed to determine the existence of these non-agricultural activities in the Gleba I of that settlement, how they are structured, the main activities carried out as sources of income and implications for these families support. The Viverde Agroecological Association is important at Gleba I of this settlement because of they help into organize it, these way was verified its performance between the land reform settlers generating income with non-agricultural activities. The environmental aspects and the presence of non-agricultural activities were investigated through a questionary with open and closed questions. The questions were maded of graphs and tables. Furthermore, interviews with the leaders of cooperatives and associations were performed. It was verified that significant part of Gleba I families income are provide from wage labor or non-agricultural activities furthermore the Viverde Agroecological Association contributes significantly to the consolidation of non-agricultural activities in the Gleba I.
Keywords: settlement; non-agricultural activities; associations; income; socioenvironmental